Development of a Rotary Collector of Fibers for a Wet Spinning Machine - Zulkifli, Ain Nadia; Soon Chin Fhong (Evolution in Electrical and Electronic Engineering, 2023)
The wet-spinning machine was used in the biomedical engineering field widely used. This project intends to design a rotary collector implemented on the wet-spinning machine and Polyacrylonitrile (PAN) as a test. The main reason for focusing this project on the development of a rotary collector of fibers processes is because the process of wet spinning producing soft fibers is crucial. Nowadays, the worker must typically supervise the process on a constant basis because it is prepared manually. The old approach required more facilities, which consumed a lot of time and energy. The aim of this project is to improve the wet spinning machine. The main objective is to design and program a microcontroller that controls the stepper motor of a rotary collector. To fulfill the objectives stated above, the scope of this project is to study the limit to the wet spinning processes to develop the rotary collector. In this project, a rotary collector will control by a stepper motor and fixed to the existing extruder machine. The length and size fiber produced can be useful in biomedical engineering by allowing the production of precise and uniform fiber structures as appropriate for use in biomedical applications such as tissue engineering and regenerative medicine. These fibers can be used as scaffolds for cellular growth, helping to create functional tissue structures for repairing or replacing damaged or diseased tissue. The uniformity and precision of the fiber structure produced by a rotary collector can also enhance the mechanical properties of the final tissue-engineered product, making it more suitable for use in biomedical applications. However, there are improvements needed to improve and optimize the functionality of this rotary collector. For example, by adding a function of several selections for the time duration of the rotary collector rotation.